Effect of Jatropha curcas seed meal inclusions in the diet of Lohmann Brown Layers on egg production and its quality - Berihun, Kefyalew; Negesse, Tegene; Tolera, Adugna (Journal of Agriculture and Environmental Sciences, 2022)
Most of the protein source feedstuffs for poultry like soybean and soybean meal are expensive. Thus alternative and cheaper non-conventional feedstuffs should be assessed in order to broaden sources of ingredients. Jatropha curcas seed meal is one of the non-conventional feed ingredients that can be used for poultry feed. Therefore, the objectives of this study were to investigate the effect of dietary inclusion of treated and untreated Jatropha seed meal on feed intake, feed conversion ratio, egg production and egg quality traits. A feeding trial was carried out for eight weeks at Hawassa University, with 250 Lohmann Brown commercial layers (42 weeks old). Chicken were allotted to five treatment diets replicated five times with 10 hens per replication in a completely randomized design. The control treatment (T1) represents the standard poultry feed that contained 42% white maize, 15% wheat bran, 7% noug cake, 25% soybean, 4% bone and meat meal, 4% limestone, 2.5% Premix and 0.5% salt. In the treatments T2 to T5, 5% of soybean seed in T1 was replaced by 1.25% untreated and treated Jatropha seed meal where T2, T3, T4 and T5 contained untreated, heat-treated, NaOH-treated and T5 yeast treated Jatropha seed meal, respectively. There were significant variations in daily feed intake, food conversion rate, hen-day egg production, hen-housed egg production and mortality among treatment groups. Chicken receiving T2 had reduced daily feed intake compared to hens that were fed on all other diets (p<0.05). Chickens reared under T1 had lower values of food conversion rate and mortality than chickens kept on all other diets (p<0.05). There was no significant differences among all treatment groups in egg shape index, egg weight and shell thickness. Substituting 5% soybean with untreated jatropha seed meal influences most of the tested parameters in the present study. On the other hand, the replacement of 5% quantity of soybean with treated jatropha seed meal had no effects on hen-daily egg production, hen-house egg production, Egg shape index, Egg weight, Shell thickness, Albumin height, Yolk height, Yolk weight and Haugh Unit compared to the standard poultry diet (T1). Accordingly, 1.25% heat, NaOH and yeast-treated jatropha seed meal could be used to replace 5% of the soybean seed in the Lohmann Brown layers diet.